SiO2–CaO rod-like particles in chitosan matrix as bioactive coatings for stainless steel implants - Katunar, María Rosa; Diaz, Florencia; Boccaccini, Aldo R.; Ballarre, Josefina (Ceramics International, 2023)
Metals have outstanding mechanical properties, being capable of supporting the combined stresses applied to biomaterials (e.g. orthopaedic implants) by the human body. Metals can be biocompatible (such as Ti or stainless steel) but they are bioinert, they generally do not generate a natural bonding with bone tissue, and it is then necessary to produce a kind of anchor or external fixation to improve the implant-bone interface. The surface chemistry and morphology of stainless steel, a material widely used for orthopaedic implants, can affect the interaction of the implant with the surrounding medium and cell attachment and growth, thus affecting the compatibility between the host tissue and the material. The aim of this work is to enhance the bioactivity of stainless steel implants by the application of a combined coating of chitosan and bioactive silica-calcia (SiCa) rod-shaped particles. Stainless steel substrates were coated in two different concentrations of SiCa particles produced by the Stöber method, immersed in a chitosan matrix via electrophoretic deposition. Thick and homogeneous coatings were achieved following the optimization of the deposition parameters, with average thicknesses between 12 and 19 μm. Although the coating exhibited fast rates of dissolution, the formation of carbonated calcium phosphate could be observed after immersion for 10 days in simulated body fluid (SBF), in microscopic images, which was confirmed via spectroscopic analysis. Murine stromal ST-2 cell proliferation was found after 4 and 10 days of seeding, indicating that the coating was not toxic and able to sustain the adhesion and growth of ST-2 cells.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Biopolymers; Cell attachment; Electrophoretic deposition; Functional coatings; Silica-calcia particles